Hubungan Karakteristik Bank dengan Harga Saham - H. Mas'ud, Muchlis; Anggarani, Dwi; Zulkifli (Bulletin of Management and Business, 2020)
This study discusses the influence of variable bank characteristics on bank stock prices included on the Indonesia Stock Exchange (2009-2013). Regarding what is used is a data collection that is a merger between cross section data and time series from 25 banks. The results showed that bad credit as a proxy for credit risk increased significantly to stock prices. Credit risk increases. It is proven that efficiency shows a negative and significant relationship to stock prices. Limitations / Implications in this study are the adequacy of bank capital, profitability and income diversification ratio non-interest income (NIIR) does not affect the bank's stock price.